Peran Mediasi Brand Satisfication terhadap Faktor-Faktor yang Dapat Memprediksi Purchase Decision - Steven Leoti Aliman; Keni Keni (Business Management Journal, 2023)
Fast Moving Consumer Good (FMCG) consists of products which are consumed frequently, thereby several FMCG firms offer products with similar benefits. Hence, in order to maintain and increase their market share, FMCG firms have to understand factors affecting consumers’ decision to purchase FMCG products. This research is aimed to empirically examine the influence of perceived value, social media marketing, and brand trust on consumer’s purchase decisions directly and indirectly through brand satisfication. Sample selection was done by using non-probability sampling method, which is convenience sampling technique on 226 consumers of shampoo in Jakarta. The questionnaire was distributed online through Google Form. Hypothesis testing was done by using PLS-SEM method. This study indicated that perceived value, social media marketing, brand trust, and brand satisfication have a positive and significant influence on purchase decision, but brand trust does not have a positive and significant influence on purchase decision. Furthermore, perceived value and brand trust have a positive and significant influence on brand satisfication, but brand trust does not have a positive and significant influence on brand satisfication. Lastly, brand satisfication can positively and significantly mediate perceived value and social media marketing on purchase decision, but it cannot positively and significantly mediate brand trust and purchase decisions.